Short Communication: A checklist of the mosquito species (Diptera: Culicidae) in the Suan Phueng District, Ratchaburi Province, Thailand - TANAWAT CHAIPHONGPACHARA (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Chaiphongpachara T. 2019. Short Communication: A checklist of the mosquito species (Diptera: Culicidae) in the Suan Phueng District, Ratchaburi Province, Thailand. Biodiversitas 20: 468-473. Mosquito is a medically important insect, which is a vector to transmit pathogens to humans. There are several methods to reduce the numbers mosquitoes, which requires entomological knowledge. It is critical to know the species of mosquitoes in the area to choose the most suitable method to provide vector control, specifically, to target mosquito species. In this study, we investigated the species of mosquito vectors in the Huay Nam Nak Village in the Suan Phueng District, Ratchaburi Province, Thailand, which is an endemic area of mosquito-borne diseases, especially malaria and dengue fever. Mosquito species were collected by the Mosquito Magnet® Independence trap from the Huay Nam Nak Village. A total of 1,002 mosquitoes, divided into eight species in four genera, including Anopheles barbirostris s.l. van der Wulp (118 individuals), An. subpictus s.l. Grassi (127 individuals), Culex quinquefasciatus Say (186 individuals), Cx. vishnui Theobald (204 individuals), Cx. whitmorei Giles (198 individuals), Aedes aegypti Linnaeus (45 individuals), Ae. albopictus Skuse (78 individuals), and Armigeres subalbatus Coquillett (46 individuals). This checklist of the mosquito species is very important information to set mosquito control measures that suit each area.